2009
DOI: 10.1183/09059180.00011104
|View full text |Cite
|
Sign up to set email alerts
|

High-altitude pulmonary hypertension: Table. 1—

Abstract: High-altitude pulmonary hypertension (HAPH) is a specific disease affecting populations that live at high elevations. The prevalence of HAPH among those residing at high altitudes needs to be further defined. Whereas reduction in nitric oxide production may be one mechanism for the development of HAPH, the roles of endothelin-1 and prostaglandin I 2 pathways in the pathogenesis of HAPH deserve further study.Although some studies have suggested that genetic factors contribute to the pathogenesis of HAPH, data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 47 publications
1
53
0
12
Order By: Relevance
“…Previous studies have reported a prevalence of high-altitude pulmonary hypertension between 5% and 18% of the population living at high altitude [52]. High-altitude pulmonary hypertension is characterized by increased pulmonary vascular resistance secondary to hypoxia-induced pulmonary vasoconstriction and vascular remodeling.…”
Section: Pulmonary Vascular Systemmentioning
confidence: 99%
“…Previous studies have reported a prevalence of high-altitude pulmonary hypertension between 5% and 18% of the population living at high altitude [52]. High-altitude pulmonary hypertension is characterized by increased pulmonary vascular resistance secondary to hypoxia-induced pulmonary vasoconstriction and vascular remodeling.…”
Section: Pulmonary Vascular Systemmentioning
confidence: 99%
“…High attitude PAH is a well-established problem in areas of the world where people live at high altitude, notably in regions of central Asia and in the Andes mountains of South America [97][98][99]. PAH is thought to be triggered, in this condition, by hypoxia.…”
Section: Principlementioning
confidence: 99%
“…In addition, other chapters will emphasise some important aspects of pulmonary vascular medicine, including pulmonary hypertension complicating hereditary haemorrhagic telangiectasia [22,23], pulmonary hypertension in high-altitude residents [24], pulmonary hypertension in children [25], chronic thromboembolic pulmonary hypertension [26], and novel therapeutic strategies such as inhaled prostaglandins [27] and soluble guanylate cyclase stimulation, an emerging option in pulmonary hypertension therapy [28]. …”
Section: Miscellaneousmentioning
confidence: 99%